A-3 Examining The Sociodemographic Factors Associated with Performance on The Community Screening Instrument for Dementia in Congolese Older Adults. (17th August 2022) - Reyes, Anny; De Wit, Liselotte; Winston, Molly R; Hammers, Dustin B; Alonso, Alvaro; Ikanga, Jean N
Abstract: Objective: Given the lack of comprehensive neuropsychological tools in Sub-Saharan Africa, there is a need to examine the clinical utility of dementia cognitive screeners in this setting. We examined the contribution of sociodemographic factors to performance on the Community Screening Instrument for Dementia (CSID) in Congolese older adults. Methods: 354 participants (mean age = 73.6 ± 6.7, mean education (years) =7.3 ± 4.7; 50% female) were randomly recruited. All participants completed the CSID (mean = 25.23 ± 4.19). Multiple linear regressions were conducted to examine the contribution of age, education, sex, and the interactions between education, school type, and participant income to CSID raw scores. Raw scores were demographically adjusted for education and sex by adding 1 point for ≤12 years of education and 1 point for female. Results: Older age (β = −0.362, p < 0.001), fewer years of education (β = −0.335, p = 0.022), female sex (β = −0.223, p = 0.035), and public schools (β = −0.185, p = 0.008) were associated with lower CSID scores. There was a trend for lower-income associated with lower CSID scores (β = −0.185, p = 0.062). The interaction between education and school was significant (p = 0.007), with education having a stronger effect on CSID scores for private (β = 0.25) relative to public schools (β = 0.16). The effect of education and sex decreased in the education- and sex-adjusted CSID scores (education β = 0.121; sex β = −0.0.056). Conclusion: We demonstrate that the effects of education on CSID varied based on sociodemographic characteristics in Congolese older adults, with private school associated with better performance. Given the effects of education and sex on performance, future studies should examine if demographically adjusted scores improve the sensitivity and specificity of the CSID in Congolese populations.